Optimasi Penggunaan Sistem Preparasi Berbantuan Gelombang Mikro pada Analisis Logam Timbal dalam Ikan Tuna Kemasan Kaleng secara Spektrofotometri Serapan Atom - Lena Bitha; Jefry Winokan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
In this paper, an efficient and rapid acid digestion method using microwave preparation system (MPS Titan 100) was to optimize and validate for determination of Lead content in canned tuna sample. The sample were digested in 6 variation of acids combination including HNO3, H2O2, and H2SO4. The digested samples were subjected to flame atomic absorption spectrophotometer for determination of Lead. The method was validated for linearity, precision, accuracy, limit of detection and limit of quantification. The optimized method showed good regression, r = 0.9997. The limit of detection and limit of quantification were found to be 0.54446 ppm and 1.8148 ppm, respectively. Precision of the method was checked by % RSD with result 0.27%. Accuracy of the method was indicated by % recovery study and resulting 109.24 % for Lead analysis. This analytical results were agreed well, as confirmed by the accepted range according to standards and guidelines. This procedure was applied to the determination lead in canned tuna sample and resulting 0.6951 ppm for A sample, 0,4634 ppm for B sample and 0.7073 ppm for C sample.